2021
DOI: 10.1111/ijn.13013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a nurse‐supervised rehabilitation programme on clinical features and systemic inflammation in Chinese children with asthma: A propensity score‐matched analysis

Abstract: Aims To evaluate whether a nurse‐supervised rehabilitation programmes could improve respiratory functions and systematic inflammation in children with asthma. Background Children with asthma always suffer from poor life quality, and physical training and pulmonary rehabilitation could be beneficial to asthma. Design A retrospective, observational, single‐centre cohort analysis. Method Baseline characteristics between the nurse‐supervised rehabilitation programme and usual‐care groups were matched by propensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Haixia found that rehabilitation training could improve FEV1%, PEF% and MMEF75/25% in children. 7 Kirkby also proposed that rehabilitation training could improve FEV1% in children. 8 These differences in further information is needed in the future to verify these observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haixia found that rehabilitation training could improve FEV1%, PEF% and MMEF75/25% in children. 7 Kirkby also proposed that rehabilitation training could improve FEV1% in children. 8 These differences in further information is needed in the future to verify these observations.…”
Section: Discussionmentioning
confidence: 99%
“…At present, respiratory rehabilitation is seldom used in children with asthma; most children received a combination of respiratory training (pursed lip breathing and Buteyko breathing) and exercise training to improve exercise ability, asthma control and quality-of-life in children. [6][7][8] However, previous research has shown that children experience difficulty in exhalation and limitations associated with exercise limitation; they are also limited by the fact that expiratory airflow can change the shape and position of the diaphragm and reduce the function of the respiratory muscles. 9 At present, there are no reports relating to the combination of respiratory muscle training to the respiratory rehabilitation program in China.…”
mentioning
confidence: 99%
“…At present, it remains controversial as to whether rehabilitation training can improve lung function. Haixia (Ha, H. X et al,2021) found that rehabilitation training could improve FEV1%, PEF% and MMEF75/25% in children. Kirkby (Kirkby, S et al,2018) also proposed that rehabilitation training could improve FEV1% in children.…”
Section: Rehabilitation Training Did Not Signi Cantly Improve Lung Fu...mentioning
confidence: 99%